Influence of remote plasma on PEDOT:PSS‐coated carbon felt for improved activity of glucose oxidase. Issue 14 (30th September 2019) - Kahoush, May; Behary, Nemeshwaree; Cayla, Aurélie; Mutel, Brigitte; Guan, Jinping; Nierstrasz, Vincent
ABSTRACT: Increasing wettability of carbon felts is an important strategy to improve their efficiency in bio‐electrochemical applications. Herein, influence of cold remote plasma (N2 + O2 ) treatment on surface properties of carbon felts with poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) coating was tested, aiming to improve immobilizing of glucose oxidase enzyme (GOx). Spectra of N 1s and O 1s confirmed the integration of carbonyl and ether as well as amide and amine groups on bare carbon fiber surface, while on coated fibers, carbonyl groups were pre‐dominant. S 2p spectra confirmed oxidation of PEDOT:PSS coating with reduction of (S − ) compared to (SO 3− ) group. GOx immobilized on different samples showed highest activity for PEDOT:PSS coating subjected to plasma with 2% O2, maintaining up to 60% after immobilization, and 37% of its activity after six cycles for some samples. Enzymes immobilized on samples without plasma treatment lost their activity after four cycles. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48521. Abstract :